Electrospun Nanofibers for Dura Mater Regeneration: A Mini Review on Current Progress - Bishweshwar Pant; Mira Park; Allison A. Kim (Pharmaceutics, 2023)
Dural defects are a common problem in neurosurgical procedures and should be repaired to avoid complications such as cerebrospinal fluid leakage, brain swelling, epilepsy, intracranial infection, and so on. Various types of dural substitutes have been prepared and used for the treatment of dural defects. In recent years, electrospun nanofibers have been applied for various biomedical applications, including dural regeneration, due to their interesting properties such as a large surface area to volume ratio, porosity, superior mechanical properties, ease of surface modification, and, most importantly, similarity with the extracellular matrix (ECM). Despite continuous efforts, the development of suitable dura mater substrates has had limited success. This review summarizes the investigation and development of electrospun nanofibers with particular emphasis on dura mater regeneration. The objective of this mini-review article is to give readers a quick overview of the recent advances in electrospinning for dura mater repair.